Direct electrical quantification of glucose and asparagine from bodily fluids using nanopores - Nicole Stéphanie Galenkamp (Nature Portfolio, 2018)
Protein nanopores are emerging as sensors for a variety of biomolecules. Here the authors develop a nanopore based on the bacterial toxin ClyA, in conjunction with binding proteins for glucose and asparagine, to detect these biomolecules simultaneously from a variety of unprocessed, diluted body fluids.